Since we're told the line is straight, the equation of the line will be of the form y = mx + c.The gradient of the line, m, is the change in y divided by the change in x ; m = (3-7)/(5-2) = - 4/3.Therefore, the line has the equation y = (-4/3)x + c, where c is an unknown value. To find c, put the x and y values of one of the co-ordinates into the equation. For example, considering (2,7) ; 7 = (-4/3)(2) + c.This equation can then be re-arranged to find c ; 7 = -8/3 + c , therefore c = 29/3Therefore, the equation of the straight line is; y = (-4/3)x + 29/3